Test of Activities of Hepatoprotector of Senggani Leaf Ethanol Extract (Melastoma Malabathricum L.) ON RAT (Rattus Novergicus) That Induced by Paracetamol - Laia, Yustina Yasnidar; Aulia, Yoridha; Sahara, Mita; Simanjuntak Masdalena, Maxwel (Biospecies, 2019)
Senggani leaves (Melastoma Malabathricum L.) are easily available plans that are sometimes used as traditional medicine. This study aimed to determine the hepatotective activity of the ethanol of senggani leaves (Melastoma Malabathricum L.) on rats (Rattus Novergicus) induced by paracetamol with histopatological parameters. Making extracts was carried out by maceration using 96% ethanol solution. The test animals used were 30 rats (Rattus Novergicus) which were divided into 6 groups. Group I without treatment, group II as negative control, group III as positive control, and group IV, V, and VI who were given senggani leaf extract, respectively 100 mg/Kg bb, 200 mg/Kg bb, and 400 mg/Kg bb for 7 day. On the 8 day all rats except group I, were induced paracetamol 180 mg/200 gr bb as the parent of liver demage. The resulst showed that the ethanol extract of senggani leaves at a dose of 400 mg/Kg bb was the most effective in hepatoprotective activity compared to a dose of 100 mg/Kg bb, and 200 mg/Kg bb with histopathological parameters induced by paracetamol.